تعـــــارض السنــة القــــوليــــة والسنـــــة الفـعــليــــــة وأثـــــره فــي اخــــتــــلاف الفــقــهـــاء دراســـة أصــوليــة فقهية تطبيــقيــة - مسعود, دالي (University of M'Sila, 2024)
الأطروحة تبحث في إشكالية تعارض السنة القولية والسنة الفعلية هل هي حقيقة أم وهمية؟ وما حقيقة هذا التعارض عند من يقول به؟ وما أثر ذلك في اختلاف الفقهاء؟ وهي من أهم البحوث الأصولية الشائكة لعلاقته المباشرة بمصداقية المصدر الثاني للتشريع الإسلامي. وتهدف الأطروحة إلى دفع شبهة تناقض السنة النبوية وبيان توافقها وبيان مناهج العلماء لدفع التعارض الظاهري. وقد خلصت هذه الأطروحة إلى نتائج غاية في الأهمية منها: أنه لا تعارض حقيقي بين السنة القولية والسنة الفعلية وأنّ التعارض إنّما هو في ذهن المجتهد وتصوره. وهو يزيد ويقل بحسب علم وفهم المجتهد وأنّ لهذا التعارض الظاهري أثر بارز في اختلاف الفقهاء كما أبرزت أنّ السنة القولية والسنة الفعلية ليست غير متعارضة فحسب، بل إنّ بعضها يكمل البعض الآخر.
The thesis Researches the problem of the conflict between the verbal Sunnah and the practical Sunnah: is it real or imaginary? and What is the truth of this conflict according to those who say it? and what effect does this have on the differences between jurists? This is one of the most important and thorny fundamentalist studies because of its direct link to the credibility of the second source of Islamic legislation. The thesis aims to eliminate suspicions of contradiction in the Sunnah of the Prophet, to explain its compatibility and to explain the methods used by scholars to repel the apparent contradiction. This study comes to very important results, including: that there is no real contradiction between the verbal Sunnah and the practical Sunnah, and that the conflict is only in the mind and perception of the diligent person. It increases and decreases according to the knowledge and understanding of the mujtahid, and this apparent contradiction has an important effect on the differences between jurists. The thesis also pointed out that the verbal Sunnah and the practical Sunnah not only are not in conflict, but rather than some of them complementing each other